1989
DOI: 10.1203/00006450-198906000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Branched Chain Amino Acids Improve Complex Maze Learning in Rat Offspring Prenatally Exposed to Hyperphenylalaninemia: Implications for Maternal Phenylketonuria

Abstract: ABSTRACT. Maternal phenylketonuria results in a high incidence of children born who are mentally retarded. It has been suggested that blood-brain-barrier transport of phenylalanine may be reduced by competitive inhibition of transporter uptake by supplemental administration of other large neutral amino acids. We hypothesized that large neutral amino acids might also be effective at improving the outcome of fetuses exposed to hyperphenylalaninemia in utero. If correct, sparing of embryonic CNS development might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The only variation was that most experiments gave 2 trials/day, in two experiments only, though, 1 trial/day was given, but the same total number of trials was used, i.e., 12. For the 2 trial/day experiments, significant CWM effects were found in hyperphenylalaninemic rats, and these deficits were mitigated by treatment with branched chain amino acids as an hypothesized therapeutic treatment (Vorhees and Berry, 1989). Other experiments showed large effects of prenatal sodium phenytoin on path-A and path-B errors (Weisenburger et al, 1990) and significant but not as large increases in errors after prenatal ethanol (Vorhees, 1988).…”
Section: Assessing Navigation In Rodentsmentioning
confidence: 99%
“…The only variation was that most experiments gave 2 trials/day, in two experiments only, though, 1 trial/day was given, but the same total number of trials was used, i.e., 12. For the 2 trial/day experiments, significant CWM effects were found in hyperphenylalaninemic rats, and these deficits were mitigated by treatment with branched chain amino acids as an hypothesized therapeutic treatment (Vorhees and Berry, 1989). Other experiments showed large effects of prenatal sodium phenytoin on path-A and path-B errors (Weisenburger et al, 1990) and significant but not as large increases in errors after prenatal ethanol (Vorhees, 1988).…”
Section: Assessing Navigation In Rodentsmentioning
confidence: 99%
“…In addition, improvements on a neuropsychologic task were shown for VIL treatment (5,39). The VIL approach was also used in an animal model of maternal PKU (40). Rats exposed to high phenylalanine levels in utero showed characteristic learning deficits, which could be prevented by VIL treatment.…”
Section: Figurementioning
confidence: 99%
“…Pratt (Pratt, 1982) reviewed the evidence to date and predicted that adding tyrosine or leucine, valine and isoleucine only, would be ineffective. Despite this, several studies in rats and humans claimed neurological/psychometric improvement with the administration of the branch chain amino acids -valine, leucine and isoleucine (Jordan, 1985;Vorhees, 1989). Experiments with 4 adult volunteers with PKU and 4 normal controls (Knudsen et al, 1995) revealed, in PKU, brain permeability to large neutral amino acids is reduced by about 50%.…”
Section: Large Neutral Amino Acids (Lnaa)mentioning
confidence: 99%
“…Both groups had similar serum levels of phenylalanine but the experimental group had lower brain levels. Further rat experiments were carried out (Vorhees & Berry, 1989), where pregnant hyperphenylalaninemic rats were given supplements valine, isoleucine and leucine. This improved performance of their offspring in a complex maze test.…”
Section: Large Neutral Amino Acids (Lnaa)mentioning
confidence: 99%